2021
DOI: 10.1177/10901981211043116
|View full text |Cite
|
Sign up to set email alerts
|

Determining Contextual Factors for a Heart Failure Self-Care Intervention: A Consensus Delphi Study (ACHIEVE)

Abstract: There is a rising recognition of the crucial role self-care plays in managing heart failure (HF). Yet patients often have difficulties implementing ongoing self-care recommendations into their daily lives. There is also recognition of the importance of theory for successful intervention design, and understanding of key factors for implementation so interventions fit a given context. Local key stakeholders can provide valuable insights to help understand relevant context-specific factors for intervention implem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 44 publications
1
6
0
Order By: Relevance
“…Six or seven sessions occurred for a period of 6 months. This is consistent with published recommendations that HF interventions should last 30 minutes and be more intensive for the first month's follow-ups 7 …”
supporting
confidence: 91%
See 2 more Smart Citations
“…Six or seven sessions occurred for a period of 6 months. This is consistent with published recommendations that HF interventions should last 30 minutes and be more intensive for the first month's follow-ups 7 …”
supporting
confidence: 91%
“…Evidence suggests that training sessions should last a minimum of 30 minutes and be scheduled more often in the short term and less frequently in the long term. 7 Finally, in light of our results, we recommend a dyadic approach to delivering MI sessions; dyad-level interventions have the intrinsic advantage of targeting processes such as coping efforts, communication, and reciprocal support behaviors between patients and caregivers.…”
Section: Ear Editormentioning
confidence: 81%
See 1 more Smart Citation
“…The intervention, which will be delived to patient and caregiver together, consists of two parts: a first and more intensive part in which four MI‐based educational sessions will be performed within 2 months; and a second and less intensive part in which the sessions will be performed at 5, 8, and 11 months from enrollment. We decided on these two parts of the intervention because in our prior experience with face‐to‐face MI (Vellone et al, 2020), four sessions in 2 months were successful in improving patient self‐care maintenance at 3 months from enrollment and because a recent Delphi survey involving several stakeholders (patients, clinicians, and policymakers) suggested that the best approach for an HF self‐care intervention would be one with more intense sessions for the first 2−3 months, followed by less intense sessions over time (Whittal et al, 2021). Conducting a study over 1 year might affect the retention of participants.…”
Section: Methodsmentioning
confidence: 99%
“…Within the context of our study, we applied the Delphi technique following qualitative interviews with key stakeholders for a heart failure (HF) behaviour change intervention (Herber et al, 2021; Whittal et al, 2021). So far, self-care interventions for improving health outcomes for patients with HF have shown mixed results (Jonkman et al, 2016), which might be due to the fact that these interventions were not theory-based or not well described for certain contexts.…”
Section: Introductionmentioning
confidence: 99%